Trauma as a Public Health Moment: Addressing Vaccine Uptake in Trauma Patients - Grace E. Keegan, BS; Rachel Alexander, BS; Simi Ogunnowo, BS; Isaiah Brown, BS; Tanya L. Zakrison, MD, MPH; Lea E. Hoefer, MD (Annals of Surgery Open)
Objective:. Our objective was to identify factors associated with COVID-19 vaccination in trauma patients and to provide an opportunity for patients to engage in conversations about vaccination. Background:. The trauma surgery service offers a unique opportunity to promote preventative health interventions in hard-to-reach populations. Methods:. Trauma inpatients in Chicago, IL were recruited for this mixed-methods study from February 2022 to April 2022. Participants completed a survey on demographics, COVID-19 vaccination status, and Experiences of Discrimination Scale adapted for medical settings. Differences between vaccinated and unvaccinated patients were analyzed using the Wilcoxon-rank sum test. A semistructured, qualitative interview was completed. Qualitative data was transcribed and analyzed using Grounded Theory Methodology. Results:. Fifty-eight trauma patients were surveyed, representing 88% of patients approached. Only 23 (40%) patients reported full vaccination to COVID-19. Previous vaccination (at least 1 dose) was associated with greater concern for COVID-19 (OR 3.47, 95% CI 1.987–6.964, P < 0.001) and higher income (OR 1.21, 95% CI 1.02–1.44, P = 0.03). Higher Experiences of Discrimination Scale scores were associated with decreased likelihood of prior vaccination (OR 0.97, 95% CI 0.95–0.99, P = 0.04). On qualitative analysis, recurrent themes included vaccination motivated by either community-based or personal health-related values, and disinterest in vaccination based on perceived low need or skepticism of experimentation. Fifteen patients (26%) eligible for a vaccine dose consented to onsite vaccination after the survey. Conclusions:. Trauma patients who have experienced more discrimination in medical settings have lower rates of COVID-19 vaccination. Vaccination rates in our population were over 2 times lower than citywide rates, but admission to the trauma service can increase comprehensive care.